Perception and attitudes towards street sexual harassment among female students of a private Human Medicine Faculty - Llerena Benites, Ruth Corazón (2016)
Objective: Determinate the perception and attitudes towards street sexual harassment among female students of the Human Medicine Faculty at San Martin de Porres University. Material and Methods: Descriptive and transversal study in which the previously validated “Likert” questionnaires, “Scale of Acceptance of Modern Myths about Sexual Aggression” and “Street Harassment Scale” where applied in a virtual way to 227 female students from the 4th, 5th, 6th academic year of the Human Medicine Faculty at San Martin de Porres University. The analysis was made in the SPSS v22 program using descriptive statistics like media, mode, tables of frequency and percentage to determine the prevalence of street harassment and the level of acceptance of beliefs about sexual harassment. Results: We found that 91% of the participants considered that they had been (sexually) harassed at least once in the last year. 48% of participants were absolutely disagree with the statements about the myths of sexual aggression. The th percentage of students that mentioned never have been harassed lowered for every year of study, from 13% in the 4 year th to 7.9% in the 6 year. Most of the students came from Central South Lima of which 88% were harassed at least once the past year. Approximately, about half of the participants, independent of the mean of transport they have used, said that they had been harassed once last year. The group of 22 years old was the most affected ¹Estudiante de la FMH USMP. Conclusion: Even though the participants considered that the Street harassment only happened a few times the past year, we didn't underestimate the fact that for almost everyone this harassment had happened at least once. Also, the majority considered to be strongly disagree regarding the myths about sexual harassment. So, it appears that street harassment, despite acting as a social problem that affects the physical and mental well-being of the Young female community, hasn't been properly managed by the authorities yet.